Grape Polyphenols Prevent Fructose-Induced Oxidative Stress and Insulin Resistance in First-Degree Relatives of Type 2 Diabetic Patients - Hokayem, Marie; Blond, Emilie; Vidal, Hubert; Lambert, Karen; Meugnier, Emmanuelle; Feillet-Coudray, Christine; Coudray, Charles; Pesenti, Sandra; Luyton, Cedric; Lambert-Porcheron, Stéphanie; Sauvinet, Valerie; Fedou, Christine; et al. (Diabetes care, 2013)
To assess the clinical efficacy of nutritional amounts of grape polyphenols (PPs) in counteracting the metabolic alterations of high-fructose diet, including oxidative stress and insulin resistance (IR), in healthy volunteers with high metabolic risk. Thirty-eight healthy overweight/obese first-degree relatives of type 2 diabetic patients (18 men and 20 women) were randomized in a double-blind controlled trial between a grape PP (2 g/day) and a placebo (PCB) group. Subjects were investigated at baseline and after 8 and 9 weeks of supplementation, the last 6 days of which they all received 3 g/kg fat-free mass/day of fructose. The primary end point was the protective effect of grape PPs on fructose-induced IR. In the PCB group, fructose induced 1) a 20% decrease in hepatic insulin sensitivity index (P < 0.05) and an 11% decrease in glucose infusion rate (P < 0.05) as evaluated during a two-step hyperinsulinemic-euglycemic clamp, 2) an increase in systemic (urinary F2-isoprostanes) and muscle (thiobarbituric acid-reactive substances and protein carbonylation) oxidative stress (P < 0.05), and 3) a downregulation of mitochondrial genes and decreased mitochondrial respiration (P < 0.05). All the deleterious effects of fructose were fully blunted by grape PP supplementation. Antioxidative defenses, inflammatory markers, and main adipokines were affected neither by fructose nor by grape PPs. A natural mixture of grape PPs at nutritional doses efficiently prevents fructose-induced oxidative stress and IR. The current interest in grape PP ingredients and products by the global food and nutrition industries could well make them a stepping-stone of preventive nutrition.